The Resurrection and early eucharistic liturgy : an investigation into the influence of the Resurrection of Jesus Christ on the eucharistic liturgy of the early Christian church - Harris, Vivian W (Rhodes University, Faculty of Divinity, Department of Divinity, 1961)
The Christian Church has always found the origin of the Eucharist to be the Last Supper of our Lord Jesus Christ with His disciples. So firmly rooted has this idea of the origin of the Eucharist become that it is commonly referred to as "The Lord's Supper"- a title with obvious reference to the Last Supper. J.H. Srawley says, "The fact that Jesus suffered at the Paschal season, that He had the Passover in mind at the Supper (Luke 22 : 15) and that He had come to be thought of as 'our Passover' (I Cor. 5 : 7) would naturally lead to the conception of the solemn memorial of His death as a Christian Passover, and this influence may have affected the Synoptists' account of the actual setting of the Supper". This tradition has persisted until the present, so that it is now generally accepted that the origin of the Eucharist is the Jewish Passover. If this is true, then the Eucharist is associated chiefly with the sacrifice and death of Jesus Christ, and there are only tenuous and indirect connections with the Resurrection of the Lord. In that case, the subject of this study would need to be abandoned. If, however, there is proof that the Eucharist is closely related to the Resurrection of Jesus Christ in origin, then it is natural to look for the influence of the Resurrection on eucharistic liturgy. Cahp. 1, p. 1.
Keywords: Liturgics; Jesus Christ in the liturgy; Lord's Supper; Resurrection